Promoting carbon neutrality in China: do financial development, foreign direct investment, and industrialization play a material role? - Yan, Jun; Li, Kaodui; Musah, Mohammed; Zhang, Lijuan; Zhou, Yutong; Gao, Dan; Akwasi Nkyi, Joseph; Gyimah Sackey, Frank; Attah Kumah, Emmanuel; Cao, Siqi; Yao, Linnan (Frontiers in Environmental Science, 2024)
One of the crucial issues confronting China is high carbon dioxide (CO2) emissions. Despite the numerous measures outlined to promote the country’s carbon neutrality target, CO2 emissions in the nation continue to increase. This means that more policy options are needed to help improve environmental sustainability (ES) in the nation. Hence, examining the relationship between financial development (FD), foreign direct investment, industrialization, and environmental sustainability in China to provide proper recommendations to drive the carbon neutrality agenda of the nation is deemed fitting. In attaining this goal, time-series data from the period 1990 to 2018 is employed. According to the results, foreign direct investment deteriorates environmental sustainability by promoting more CO2 emissions. This validates the pollution haven hypothesis (PHH). In addition, industrialization and financial development are not friendly to the nation’s environmental quality. Furthermore, economic growth and urbanization escalate environmental pollution in the nation. In addition, the interactions between financial development and foreign direct investment and between financial development and industrialization deteriorate the environment in China. Moreover, foreign direct investment and financial development have an inverted U-shaped association with environmental degradation, but industrialization and environmental pollution are not nonlinearly related. The study advocated for the implementation of measures that could help advance the carbon-neutrality targets of the nation.